Impact of Seasonal Variations on the Hemostatic System in COVID-19 - T.A. Bobomuratov; M.A. Bakirova; M.A. Ernazarova (Zien Journals, 2025)
At present, improving medical care for children during the recovery period after COVID-19, reducing post-recovery complications, and preventing their occurrence remain a priority direction in both scientific and practical pediatrics. The causative agent of COVID-19 induces inflammation and enhances blood coagulation. Researchers have warned that SARS-CoV-2 may damage blood vessels in children, potentially leading to the future development of hypertension, pulmonary hypertension, stroke, and chronic kidney disease.
Keywords: COVID-19; hypercoagulability; children; season